PENGUNGKAPAN LINGKUNGAN: DITINJAU DARI KINERJA LINGKUNGAN, UKURAN PERUSAHAAN, LEVERAGE DAN IMPLIKASINYA TERHADAP PROFITABILITAS - Putri, Lismi Nugraheni; Rustiana, Siti Hamidah; Tarmizi, Muhammad Irfan (Balance : Jurnal Akuntansi dan Bisnis, 2024)
This research was conducted to determine the relationship between environmental performance, company size, and leverage on environmental disclosure and its implications on profitability in PROPER-rated companies listed on the Indonesia Stock Exchange for the 2019-2023 period using secondary data, namely annual financial report data. The type of research used is associative research. The population in this study was 67 companies and the samples taken were 11 companies. The data collection technique used is documentation. The data analysis method in this research is a quantitative analysis using several techniques, namely classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing assisted by data processing applications, namely Statistical Product and Service Solutions (SPSS). The results show that environmental performance and leverage influence environmental disclosure, however, company size doesn’t influence environmental disclosure. Furthermore, leverage influences profitability, but environmental performance, company size, and environmental disclosure don’t.